1990
DOI: 10.1097/00000658-199002000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Distal Splenorenal Shunt Versus Endoscopic Sclerotherapy in the Prevention of Variceal Rebleeding First Stage of a Randomized, Controlled Trial

Abstract: In 1984 we started a prospective controlled trial comparing endoscopic sclerotherapy (ES) with the distal splenorenal shunt (DSRS) in the elective treatment of variceal hemorrhage in cirrhotic patients. The study population included 40 patients with cirrhosis and portal hypertension referred to our department from October 1984 to March 1988. These patients were drawn from a pool of 173 patients who underwent either elective surgery or endoscopic sclerotherapy during this time. Patients were assigned to one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 30 publications
1
17
1
1
Order By: Relevance
“…The rebleeding rate from portal hypertension has been found to range from 3% to 18% in patients treated with surgical shunts and followed-up for a mean period of 28 to 60 months. 30,31 In our meta-analysis, the combined rebleeding rate after TIPS was 19%, only slightly higher than those reported after surgical shunts; however, the mean follow-up periods after TIPS were much shorter, less than 20 months in all but 2 studies (25 and 32 months). 16,23 The rebleeding rate after TIPS is anticipated to increase with time because of a progressive increase in the rate of stent dysfunction (stenosis or occlusion) within at least the first 3 years.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The rebleeding rate from portal hypertension has been found to range from 3% to 18% in patients treated with surgical shunts and followed-up for a mean period of 28 to 60 months. 30,31 In our meta-analysis, the combined rebleeding rate after TIPS was 19%, only slightly higher than those reported after surgical shunts; however, the mean follow-up periods after TIPS were much shorter, less than 20 months in all but 2 studies (25 and 32 months). 16,23 The rebleeding rate after TIPS is anticipated to increase with time because of a progressive increase in the rate of stent dysfunction (stenosis or occlusion) within at least the first 3 years.…”
Section: Discussioncontrasting
confidence: 52%
“…This is not surprising, because TIPS is a portosystemic shunt; the incidence of encephalopathy in patients with distal splenorenal surgical shunts has been reported between 16% and 34% and in those with surgical portosystemic shunts above 40%. 30,31 There was no common trend for days of hospitalization; some reported that patients randomized to TIPS 13,15,16 spent more days in hospital, whereas others reported that patients randomized to ET 14,23,25 spent more days in hospital during follow-up. Patients randomized to ET had a mean of 3 to 4 sessions for varice eradication and a surveillance endoscopy every 3 to 6 months thereafter, whereas patients randomized to TIPS had many Doppler ultrasounds, at least 2 to 3 angiographies within the first year, and several stent interventions for asymptomatic or symptomatic stent dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…96,98,113,114,116,117 Data indicate Ն90% control of bleeding with all types of surgical shunt. Encephalopathy and liver failure rates are dependent on underlying liver disease and the loss or maintenance of portal perfusion.…”
Section: The Role Of Endoscopic Ultrasonography In Patients With Esopha-mentioning
confidence: 98%
“…Surgical shunts have received renewed interest in the 1990s because of their effectiveness in preventing rebleeding. 96,98,[109][110][111][112][113][114] Bleeding is controlled in 90% to 95% of patients. Data on surgical shunts in the 1990s indicate better outcomes than earlier reported series in the literature primarily because of better patient selection.…”
Section: Henderson Jm (Chair) Blei a Bosch J Orloff Mj Rikkers Lmentioning
confidence: 99%
“…[7.22.25.34]. In fünf der sieben Studien war die Überlebenszeit bei beiden Modalitä ten gleich [25,[34][35][36][37], In zwei Studien der Emory-Gruppe aus At lanta (USA) wurde bei allen Sklerosierungsversagern, die in 30% der Fälle auftraten, eine Shuntoperation vorgenommen [22. 33].…”
Section: Discussionunclassified